Transmission of multiwave laser radiation to the investigated volume through dense aerosol layers; Journal of Applied Mechanics and Technical Physics; Vol. 52, iss. 4 - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Vlasov V. A. Viktor Alekseevich; Khan V. A. Valery Alekseevich; Lenskii V. N. Vladimir Nikolaevich (2011, 2011)
Title screen